2014
DOI: 10.1002/jsfa.7042
|View full text |Cite
|
Sign up to set email alerts
|

Caseinate–gelatin and caseinate‐hydrolyzed gelatin composites formed via transglutaminase: chemical and functional properties

Abstract: The composites generated were different in chemical characteristics and better in viscosity and emulsion stability than original caseinate. They might have potential as protein thickeners and emulsifiers. CLSM is a better technique to assess emulsion stability of food proteins than the classic turbidity method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Gelatin films cross-linked by glutaraldehyde (Bigi, Cojazzi, Panzavolta, Rubini, & Roveri, 2001) and dialdehyde alginate (Boanini, Rubini, Panzavolta, & Bigi, 2010) were reported to have increased thermal stability at higher denaturation temperatures (up to 30°C for glutaraldehyde, and 3°C for dialdehyde alginate). TGase-induced cross-linking was reported to enhance the thermal stability of caseinate (Luo & Zhao, 2014) and β-lactoglobulin in heat-shocked whey proteins (Damodaran & Agyare, 2013). The present study shares the same conclusions as these studies: cross-linked gelatin showed higher resistance to thermal treatment due to dityrosine formation in its molecules.…”
Section: Thermal Stability Of Cross-linked Gelatinsupporting
confidence: 87%
See 1 more Smart Citation
“…Gelatin films cross-linked by glutaraldehyde (Bigi, Cojazzi, Panzavolta, Rubini, & Roveri, 2001) and dialdehyde alginate (Boanini, Rubini, Panzavolta, & Bigi, 2010) were reported to have increased thermal stability at higher denaturation temperatures (up to 30°C for glutaraldehyde, and 3°C for dialdehyde alginate). TGase-induced cross-linking was reported to enhance the thermal stability of caseinate (Luo & Zhao, 2014) and β-lactoglobulin in heat-shocked whey proteins (Damodaran & Agyare, 2013). The present study shares the same conclusions as these studies: cross-linked gelatin showed higher resistance to thermal treatment due to dityrosine formation in its molecules.…”
Section: Thermal Stability Of Cross-linked Gelatinsupporting
confidence: 87%
“…Thermogravimetric (TG) analysis of the samples was carried out using a TG analyser (SDT Q600, TA Instruments Inc., New Castle, DE, USA) as previously reported (Luo & Zhao, 2014), with slight modification. Dried samples were maintained in a desiccator at room temperature with saturated NaCl solution (relative humidity~75.5%) for 72 h, to ensure that the samples adsorbed water completely.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Thermogravimetry analysis is a useful tool to describe thermal behaviour and stability of synthetic polymers, organic materials and biopolymers during heating . TG and DTG were also used in a previous study to show successfully that conjugation of the plastic gelatin products into casein by TGase brought about lower thermal stability . It was found that deamidation decreased thermal stability of betaB1‐crystallin, supporting that GC‐DSPI1 and GC‐DSPI2 (as two deamidated protein products) were less stable than GC‐SPI.…”
Section: Resultsmentioning
confidence: 96%
“…The transparency of treated FSG-HMP solution was determined by the measurement of turbidity using a UV-visible spectrophotometer (Evolution Array, Thermo-Scientific, Waltham, MA, USA) at a wavelength of 600 nm according to the method of Luo et al 21 Double-distilled water was used as the blank reference. Each turbidity measurement was carried out in triplicate and calculated as follows:…”
Section: Transparency Measurementsmentioning
confidence: 99%